The Effect Of Teams Games Tournaments Model In Arabic Language To Increase Student Motivation and Learning Outcomes - Istiqomah, Dhia; Bahruddin, Uril; Qomari, Nur (JURNAL IJ-ATL, 2025)
Creating an enjoyable learning atmosphere is very necessary in this era, especially in learning Arabic in order to increase students' motivation and learning outcomes. Researchers used the Teams Games Tournament (TGT) type cooperative learning model as the right solution to stimulate students' enthusiasm for learning and critical thinking. This study aims to determine the effect of Teams Games Tournaments (TGT) model to improve motivation and learning outcomes of Arabic language. Researchers used the Quasi Experiment method with pretest-posttest group design. The sample in this study consisted of 52 students who were divided into two classes, namely class A as an experimental class consisting of 26 students and class B as a control class of 26 students. The results of this study indicate an increase in learning motivation and student learning outcomes in Arabic language learning. This is evidenced by the hypothesis test where the sig value is 0.000 <0.05 so that H0 is rejected and Ha is accepted, so there is an effect of the Teams Games Tournaments (TGT) model to increase student motivation and learning outcomes in Arabic language learning.